DEVELOPING GABILPANET-BASED NUMBER LINE LEARNING MEDIA TO ENHANCE ELEMENTARY SCHOOL STUDENTS’ UNDERSTANDING OF THE CONCEPT OF INTEGERS COUNTING OPERATION AT GRADE VI - Farida Zakiah; Sukirman; Sri Utaminingsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this research was to analyze the effectiveness of gabilpanet-based number line learning media to enhance elementary school students’ understanding of the concept of integer counting operations at grade IV in Kabupaten Jepara. This research was a development research using Borg & Gall model. The development steps included: 1) researching the existing products, 2) studying the literature, 3) planning the product development, 4) designing the product, 5) conducting limited trial, 6) conducting main field trial, 7) conducting operational field trial. The subjects of this study were sixth grade students at SDN 4 Tulakan, SDN 2 Bandungharjo, SDN 3 Bandungharjo, and SDN 4 Bandungharjo. Data were collected through observation, questionnaires, tests, and interviews. Then, the validation results were analyzed by accumulating the scores and the statistical test of the effectiveness was carried out with SPSS version 26. Data on the effectiveness of gabilpanet-based number line learning media were analyzed through normality and homogeneity tests at a significance level of 0.05. The finding revealed that gabilpanet-based number line learning media was effective and useful to be utilized in learning activities in order to enhance studetns’ understanding of the concept of integer counting operations. Based on the data obtained, the average score of students’ learning activities was 0.76 with a percentage of 76%. Moreover, the result of students’ learning outcome based on the average score of n-Gain was 0.69 with an average pre-test score of 43.00 and the average post test 82.50.